The Impact of Type II Diabetes on Tongue Dysplasia and p16-Related Aging Process: An Experimental Study - Eren Altun; Hasmet Yazici; Erhan Arslan; Kamil Gokce Tulaci; Haydar Ali Erken (Analytical Cellular Pathology)
Objective. To evaluate the effect of streptozotocin-induced experimental diabetes mellitus on p16, p53, Ki67, and Bcl2 expressions and histopathological changes in the tongue of the rats. Material and Methods. Twenty-two adult female Sprague-Dawley rats were used. The rats were randomly divided into 2 groups (n=14) as control (C) (n=8) and diabetic (DM) (n=6). The rats in the DM group were given streptozotocin as a single intraperitoneal dose for induction of diabetes. Histopathological and immunohistochemical evaluations of formalin-fixed and paraffin-embedded tissue sections of the tongue were used. Results. Significant differences were observed between the DM group and the control group in terms of epithelial thickness, length of filiform papillae, and width of filiform papillae (p=0.005, p=0.001, and p=0.006, respectively). There was no significant difference between the groups in terms of mononuclear inflammatory cell infiltration, capillary proliferation, and dysplasia (p=0.204, p=0.244, and p=0.204, respectively). As a result of immunohistochemical studies, no significant difference was found between the groups in terms of p53, Ki67, and Bcl-2 expressions (p=0.588, p=0.662, and p=0.686, respectively). A significant difference was found between the groups when p16 expression was evaluated (p=0.006). Conclusions. In our study, streptozotocin-induced experimental diabetes mellitus induced p16 expression but did not show any difference in p53, Bcl-2, and Ki67 levels. It should be considered in the studies that the pathological changes at the early stages of the relationship between DM and oral cancer may be related to p16 expression; however, it may also be linked with p16-related aging process.